LEARNING AND EARNING:EXPLORING THE ECONOMIC BENEFITS OF DIFFERENT LEVELS OF EDUCATION IN PAKISTAN - Yasmin, Fouzia; Ashraf, Ayesha; Ashraf, Iqra; Irshad, Maryam (The journal of contemporary issues in business and government, 2021)
This paper inspects the role of educational achievement, both on an aggregate and disaggregated level on economic growth in Pakistan. Diversity in literacy rates will produce different outcomes. As many individuals with higher education get higher returns from their education level. Investment in education produces skilled and efficient manpower making it approachable for any country to achieve economic objectives i.e. sustainable economic growth and development. Data for the empirical analysis has been taken from 1976-2020 on annual basis. Auto-Regressive Distributed Lag (ARDL) Approach to Cointegration was applied for the analysis and it was concluded that middle and higher education levels produce a higher return to the economy as a whole. So, the investment must be made to enhance the overall economic gains.